A Study focused on how Korean IT Service Firms were financially impacted since the restrictions on participation of large firms - Choi, Hyun-Taek; Ryu, Gab-Sang (International Journal of Engineering and Technology, 2018)
The restriction of participation in public informatization projects by firms with cross-shareholding restrictions in the Republic of Korea, was enforced in January 2013. This study analyzes the financial performances of small and medium sized IT firms in Korea three years prior and 3 years after the restrictions on participation of large firm. We verified whether there were any differences between medium and small IT service firms before and after restrictions on participation of large firms. A sample of 121 small and medium-sized IT services firms were classified into 3 groups and statistical techniques (T-test and one-way ANOVA) were used for the purpose of the analysis. In the three years after the restriction of participation of large corporations, the total assets and sales of the medium and small IT service firms were positive, but the operating profit and net profit were negative. Particularly, the negative effects were more pronounced for medium-sized. The reduction effect of medium and small-sized IT service firms is different from the first legislative purpose of enforcing the restriction system of large enterprises, so we suggest the policy to be revised.Â